Applicability Analysis of Pre-cracked Material for SHPB during the High-level Radioactive Waste Geo-disposal. Issue 4 (July 2021) - Gao, Huan; Liu, Chang; Man, Ke
Abstract: According to the national nuclear power plan, the high-level radioactive waste should be disposed safety and effectively. And the deep geological disposal is the main way, which is influenced by the surrounding rock and soil, especially the physical and mechanical properties. Currently, the SHPB is mature equipment for the material's dynamic testing. It is mainly used to load the entire specimen, however, the specimen with the pre-crack is less used. Firstly, it should satisfy two hypotheses, i.e. the one dimension stress wave and the stress equalization when using the SHPB to measure the mechanics characteristics of the material, especially for the pre-cracked specimen. Then, from the point of stress equalization along the specimen, emphasize the importance of the dynamic force equilibrium during the testing data processing. Finally, the SHPB testing system could also be applied to the pre-cracked specimen has been proposed.